A Mixed Methods Approach to Evaluate Partnerships and Implementation of the Massachusetts Prevention and Wellness Trust Fund - Rebekka M. Lee; Rebekka M. Lee; Shoba Ramanadhan; Shoba Ramanadhan; Gina R. Kruse; Gina R. Kruse; Charles Deutsch (Frontiers Media S.A., 2018)
Background: Strong partnerships are critical to integrate evidence-based prevention interventions within clinical and community-based settings, offering multilevel and sustainable solutions to complex health issues. As part of Massachusetts' 2012 health reform, The Prevention and Wellness Trust Fund (PWTF) funded nine local partnerships throughout the state to address hypertension, pediatric asthma, falls among older adults, and tobacco use. The initiative was designed to improve health outcomes through prevention and disease management strategies and reduce healthcare costs.Purpose: Describe the mixed-methods study design for investigating PWTF implementation.Methods: The Consolidated Framework for Implementation Research guided the development of this evaluation. First, the study team conducted semi-structured qualitative interviews with leaders from each of nine partnerships to document partnership development and function, intervention adaptation and delivery, and the influence of contextual factors on implementation. The interview findings were used to develop a quantitative survey to assess the implementation experiences of 172 staff from clinical and community-based settings and a social network analysis to assess changes in the relationships among 72 PWTF partner organizations. The quantitative survey data on ratings of perceived implementation success were used to purposively select 24 staff for interviews to explore the most successful experiences of implementing evidence-based interventions for each of the four conditions.Conclusions: This mixed-methods approach for evaluation of implementation of evidence-based prevention interventions by PWTF partnerships can help decision-makers set future priorities for implementing and assessing clinical-community partnerships focused on prevention.